Eurocentrism - Wintle, Michael J., author.
1 online resource (xii, 292 pages)
Keywords: "This book raises awareness of Eurocentrism's enormous impact and shows how, over the course of five centuries, Eurocentrism has extended its power across the globe. By exploring a vast range of sources including Eurocentric maps and images, historiography, and Rudyard Kipling's White Man's Burden, Wintle uncovers Eurocentrism's gradual evolution and reveals the ways in which it functions at both seen and unseen levels. Due to its multi- and interdisciplinary analysis, this book is an indispensable tool for both scholars and students concerned with modern history, politics, visual culture and political geography"--